The impact of lockdown and changes in clinical practice on glycemic control during the COVID-19 pandemic: Analysis of data from the National Diabetes Center, Doha, Qatar - Alowainati, Buthaina; Dabbous, Zeinab; Salameh, Obada; Hamad, Mohammad; Al Hail, Layla; Abuheliqa, Wajeeha; AL-Janahi, Ibrahim; Jayyousi, Amin; Zirie, Mahmoud (Journal of Diabetes and Endocrine Practice, 2021)
Introduction: The coronavirus disease-2019 (COVID-19) pandemic was associated with international obligations that modified lifestyles and clinical practice. These changes are worrisome for patients with diabetes, as disruption from a routine can have devastating effects on glucose control. This retrospective study aims to assess the impact of lockdown and the efficacy of the instituted changes in patient management on blood sugar control. Methods: Patients with type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) who received management through telemedicine at the National Diabetes Center over a lockdown period of 3 months were included. The blood investigations that were done for them as part of standard care were reviewed. Results: A total of 509 patients were included. HbA1c slightly decreased in 49.5% of the patients after the lockdown (P = 0.42). Patients who were not hypertensive experienced a significant reduction in HbA1c (adjusted odds ratios [ORa]: 0.59, 95% confidence interval [CI]: 0.39–0.91, P = 0.018) during the lockdown. A significant association between body mass index (BMI) and lower HbA1c level postlockdown was also determined (ORa: 0.95, (95% CI: 0.92–0.98, P = 0.001). A significant HbA1c reduction was only noted in the BMI group of normal weight (mean: 0.46 ± 0.3, P = 0.03). Conclusion: The imposed lockdown due to COVID-19 did not adversely impact the HbA1c level and glycemic control in T1DM and T2DM patients. Inversely, HbA1c improvements were determined in patients with normal weight and blood pressure after the lockdown period.
Keywords: Coronavirus disease-2019; diabetes; HbA1c; lockdown; telemedicine